A giant mucinous cystadenocarcinoma of the appendix: a case report and review of the literature. Issue 1 (December 2016) - Nagata, Hiroshi; Kondo, Yuji; Kawai, Kazushige; Ishihara, Soichiro; Kazama, Shinsuke; Nirei, Takako; Soma, Daisuke; Yamada, Jun; Sunami, Eiji; Kitayama, Joji; Kubota, Yoshiro; Watanabe, Toshiaki
Abstract Background Mucinous cystadenocarcinoma is the second most common etiology of appendiceal mucocele. We report a relatively rare case of a giant appendiceal mucocele caused by mucinous cystadenocarcinoma, which occupied the entire abdomen of an adult woman. Case presentation A 63-year-old woman presented with a chief complaint of abdominal distention. Imaging studies showed a giant cystic mass occupying her entire abdomen. Laparotomy confirmed a giant appendiceal mucocele, and the patient underwent ileocecal resection. A mucinous deposit was not found in her abdominal cavity, and the ovaries were grossly normal bilaterally. The pathological diagnosis was mucinous adenocarcinoma with a low-grade mucinous neoplasm that invaded the subserosa. Regional lymph node metastasis was not found. She has had recurrence-free survival for 5 years. Conclusions The present case is the largest appendiceal cystadenocarcinoma ever reported. The optimal treatment of an appendiceal neoplasm requires further research based on consensus terminology of an appendiceal mucocele.